The impact of Atopic Dermatitis on the mental health of the pediatric population: An integrative review (Research, Society and Development, 2024)
Objective: To analyze data in the current literature on atopic dermatitis in children and adolescents and its psychological repercussions in these groups. Methodology: This is an integrative literature review conducted in major health databases using the following Boolean operators: "Atopic Dermatitis" AND "Child" OR "Adolescent" AND "Mental Health" OR "Mental Disorder". Results: Primarily, 186 articles were found from the search across 3 databases, of which 18 articles were included following the proposed inclusion and exclusion criteria, with a filter for studies from the last five years, for the final study composition. Conclusion: An intimate relationship between atopic conditions, especially Atopic Dermatitis, and compromised mental health in the studied group was demonstrated, primarily due to repercussions on self-esteem, mood, interpersonal relationships, and cognitive and academic development. The most prevalent disorders included attention deficits, depression, and anxiety. Therefore, multidisciplinary monitoring throughout the pediatric population from the diagnosis of this condition is essential to prevent or minimize the progression of psychiatric conditions and their complications.